Adaptive expertise and creative thinking: A synthetic review and implications for practice. (March 2020) - Gube, Maren; Lajoie, Susanne
Highlights: Flexible thinking skills are critical for graduates in rapidly changing world. Teaching and learning innovation skills and competencies in higher education. Applied Creative Thinking: synthesis of creative thinking and adaptive expertise. Applied Creative Thinking: using acquired knowledge creatively and adaptively. Transformative teaching, active learning, error framing support ACT. Abstract: To thrive in a rapidly changing society, university graduates need flexible thinking skills. Such skills have been explored in diverse bodies of literature, with different names, through different lenses. This article presents a critical review and synthesis of theories in two distinct bodies of the research literature: adaptive expertise and creative thinking. Based on our analysis, we propose that the two constructs overlap as "applied creative thinking", denoting the kind of creativity that occurs when learned knowledge or acquired expertise is used adaptively and creatively. Implications for teaching and learning in higher education achievement settings are discussed, and directions for future research are suggested to better understand factors influencing the skills and competencies needed by graduates in an innovation society.